2020
DOI: 10.1111/spsr.12405
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up Deliberation: Testing the Potential of Mini‐Publics to Enhance the Deliberative Capacity of Citizens

Abstract: This paper tests the possibility of embedding the benefits of minipublic deliberation within a wider voting public. We test whether a statement such as those derived from a Citizens' Initiative Review (CIR) can influence voters who did not participate in the pre-referendum minipublic deliberation. This experiment was implemented in advance of the 2018 Irish referendum on blasphemy, one of a series of social-moral referendums following the recommendations of a deliberative assembly. This is the first applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…The citizens’ assembly in turn serves as a “recommending force” or “body of trustees” to the broader public (Mansbridge et al, 2012 ; Warren and Gastil, 2015 ). There is growing evidence from the United States (Gastil et al, 2016 ; Ingham and Levin, 2018 ), Canada (Boulianne, 2018 ), and Ireland (Suiter et al, 2020 ) that mini-publics are indeed effective at generating support among the broader public. Such endorsement is thought to rely on different processes, including trust—the broader public perceiving the mini-public as representative, hence trustworthy—and heuristics—assuming some division of cognitive labor is inevitable in democratic decision-making, the broader public can thus rely on “information cues” produced by the mini-public (MacKenzie and Warren, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The citizens’ assembly in turn serves as a “recommending force” or “body of trustees” to the broader public (Mansbridge et al, 2012 ; Warren and Gastil, 2015 ). There is growing evidence from the United States (Gastil et al, 2016 ; Ingham and Levin, 2018 ), Canada (Boulianne, 2018 ), and Ireland (Suiter et al, 2020 ) that mini-publics are indeed effective at generating support among the broader public. Such endorsement is thought to rely on different processes, including trust—the broader public perceiving the mini-public as representative, hence trustworthy—and heuristics—assuming some division of cognitive labor is inevitable in democratic decision-making, the broader public can thus rely on “information cues” produced by the mini-public (MacKenzie and Warren, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is empirical evidence that participants from the wider public process objective information provided from a mini-public quite differently than the members of this mini-public. In some cases, it dampens their factual knowledge, but it has also been shown to positively increase people's empathy towards the other side [40]. Moreover, using climate assemblies instrumentally to garner support may lead to cherry-picking of results [29].…”
Section: Ideal 3: Deliberative Quality Practice 3: One-sided Problem ...mentioning
confidence: 99%
“…Johnson, Morrell and Black (2019) analyzed participant surveys and observer notes from three further CIRs and concluded that during the four-day deliberation enthusiasm was common throughout, happiness steadily increased, anxiety peaked early, sympathy was moderately present, anger was moderately present and peaked on day three, and sadness was uncommon; they theorize that deliberative procedures were likely key in explaining these results. Suiter et al (2020) utilized a survey experiment and discovered that even non-participants who read balanced information generated by a CIR had greater affective empathy for the other side of the policy debate.…”
Section: Recent Developmentsmentioning
confidence: 99%